Drying of industrial ceramic bricks and process parameter estimation: an advanced concentrated approach (Research, Society and Development, 2020)
This work aims to study the drying of porous and arbitrarily shaped solids using the concentrated analysis method. An advanced phenomenological mathematical model based on concentrated analysis and its exact solution are presented to predict the mass and heat transfers in industrial hollow ceramic bricks and to estimate the transport coefficients. Different simulations were carried out to evaluate the effect of air temperature on the drying process. Transient results of the moisture content and temperature of the brick, and of the convective heat and mass transfer coefficients are presented and discussed. It was found that the higher the temperature the greater the convective heat and mass transfer coefficients on the brick surface, and the faster the product loses moisture and raises its temperature. From the study, an optimized drying condition of the industrial ceramic brick is proposed in order to minimize defects in the post-drying product, increase its quality for the firing step, and reduce waste of raw material and save energy in the process.